Correlations between the detection of e antigen or antibody and electron microscopic pattern of hepatitis B surface antigen (HBsAg) associated particles in the serum of HBsAg carriers. - Trepo, C (1977)
The distribution of HBsAg associated particles, especially the presence of Dane particles, was studied by electron microscopy in coded sera of 68 chronic HBsAg carriers. Results were correlated with the detection of eAg or Ab and clinical diagnosis. Sera from haemodialysis and chronic hepatitis patients showed a high prevalence of e antigenaemia (9/13, 69-2% and 8/19, 42-1%) and Dane particles (11 and 16 respectively, 84%). By contrast, out of 36 chronic asymptomatic carriers of HBsAg, 28 (77-7%) were positive for e antibody but only 1 (2-7%) had eAg. Dane particles were found in 13/36 (36-1%). A statistically significant correlation was observed between the detection of eAg and the presence of Dane particles (94-4%) in the serum. However, Dane particles were still observed in 10/28 (35-7%) of anti-e positive sera. The data suggest that eAg may be linked to complete HB virions.